PEMAHAMAN WASIT TERHADAP PERUBAHAN PERATURAN PERMAINAN BOLABASKET PASAL 25 TRAVELLING DARI TAHUN 2014 KE TAHUN 2017 - dewi, reza retno; Wismanadi, Himawan (Jurnal Kesehatan Olahraga, 2019)
Basketball is a sport that played by hand with a large ball which consists of 2 teams and each team consists of 5 people intersecting in the field. In the basketball game led by 3 referees consisting of 1 chief crew and 2 officials. The quality of matches also determined by the role of a referee, therefore the referee must be able to understand and apply all regulations issued by the Federation International Basketball Association (FIBA) which has been socialized by PB PERBASI. There were a number of changes in the 2017 basketball rules from 2014, one of it was traveling. The changes such as the number of steps, in the rules of the 2014 basketball game using 2 steps while in 2017 using 3 steps (with the name 0 steps). The aim of this study was to determine the level of referee's understanding of rules changing in the basketball game article 25 traveling from 2014 to 2017 at the referee of UKM basketball club in the State University of Surabaya that licensed by Perbasi. The type of research used in this study is quantitative descriptive with questionnaires as research instruments given to referees of UKM basketball in the State University of Surabaya with a sample of 10 referees. Based on the results of the study, it can be concluded that the total average comprehension of referees is 74%, this shows that the referee's understanding in the UKM of the State University of Surabaya is quite good. Keywords : Basketball, basketball referee, traveling, understanding